Unveiling the Digital Revolution: Assessing the Dynamic Impact of E-Banking Adoption among Generations Y and Z in Malaysia - Yahaya, Siti Norbaya; Bakar, Mohd Hafiz; Bakri, Mohammed Hariri; Jaafar, Johanna Abdullah; Hishamudin, Nurul Shahirah (Journal of Ecohumanism, 2025)
This study investigates the influence of e- banking based on the perspective of Generations Y and Z, with a specific emphasis on their adeptness with technology. The research conducted a quantitative study with 384 Malaysian participants, which revealed that these generations exhibit a high level of familiarity with digital technology and enthusiastically use e-banking due to its convenient and time-saving advantages. Nevertheless, the implementation of the technology is impeded by issues over security, privacy, and trust. The research also evaluates the impact of age, education, and money on their viewpoints. The findings indicate that resolving these issues might improve the adoption of e-banking, which would be advantageous for banks, regulators, and academics. The study proposes the elimination of obstacles to enhance e-banking and promote financial inclusion among Generations Y and Z, providing valuable guidance for policymakers to formulate regulations that safeguard consumers. Subsequent studies may broaden the assessment of electronic banking among diverse client segments. Furthermore, the data collected from participants was analyzed using the Statistical Package for Social Sciences (SPSS). The researcher used descriptive statistics, Pearson's correlation coefficient, and multiple regression analysis to examine the hypothesis. The study found that perceived usefulness, perceived ease of use, perceived data security and privacy, and perceived technology and innovation all have a significant impact on the usage of e-banking among Generation Y and Z. Among these factors, perceived technology and innovation was found to be the most influential in driving the adoption of e-banking among Generation Y and Z. In future research, the researchers might use the suggested novel conceptual framework to conduct the investigation or incorporate other variables for examination.